John Cunningham Virus T-Antigen Expression on Mild and Severe Dysplasia Adenomatous Polyp, Low and High Grade Adenocarcinoma of The Colon - Dyonesia Ary Harjanti; Cyprianus Murtono; Kidyarto Suryawinata; Angelina Halim; Michelle Felicia Wiryokusuma; Timotius Benedict Djitro (Molecular and Cellular Biomedical Sciences, 2019)
Background: John Cunningham Virus (JCV) was involved in pre-malignant lessions and carcinogenesis of the colon. The purpose of this study was to detect and analyze JCV T-Ag expression in mild and severe dysplasia adenomatous polyp as well as low and high grade adenocarcinoma of the colon.Materials and Methods: This study used analytic descriptive, cross sectional approach. The samples’ paraffin blocks were taken from colon adenomatous polyp cases (all grades of dysplasia) and cases of colon adenocarcinoma (all degrees) at Anatomical Pathology Laboratory, School of Medicine, Atma Jaya Catholic University of Indonesia from 2010-2014 (5 years period). Samples were reviewed from HE slides to determine histopathologic diagnosis, grades of dysplasia and grading. We performed immunohistochemistry staining with monoclonal antibody anti–SV 40-T-Ag to detect JCV T-Ag expression.Results: We found 7 cases of colon adenomatous polyp, of which 4 (57%) were mild dysplasia and 3 (43%) were severe dysplasia. Positive expression of JCV T-Ag was detected in 1 (14%) mild dysplasia case. Data analysis using Fischer’s Exact Test was p>0.05. We also found 16 cases of colon adenocarcinoma. 14 cases (87.5%) of low grade variant and 2 cases (12.5%) of high grade variant. Positive expression of JCV T-Ag was detected in 2 (12.5%) low grade cases. Data analysis using Fischer’s Exact Test was p>0.05.Conclusion: There was no difference of JCV T-Ag expression in colon adenomatous polyp (mild-severe dysplasia) and colon adenocarcinoma (low-high grade) cases at Anatomical Pathology Laboratory School of Medicine, Atma Jaya Catholic University of Indonesia 2010-2014.Keywords: colon adenomatous polyp, adenocarcinoma, JCV T-Ag